A Gender Employment Gap Index (GEGI) : A Simple Measure of the Economic Gains from Closing Gender Employment Gaps, with an Application to the Pacific Islands - Pennings, Steven Michael (Washington, DC: World Bank, 2022)
Despite a policy consensus that closing gender employment gaps will boost economic growth, relatively little is known about the size of these gains in many developing countries. This paper develops a new Gender Employment Gap Index (GEGI), which is equal to the size of long-run GDP per capita gains from closing gender employment gaps. The GEGI is simple and transparent and can be easily constructed using closed-form expressions for almost all countries using macroeconomic employment rate data by gender. The basic variant of the GEGI is the gap between male and female employment as a share of total employment. The full GEGI is similar, but instead of using an aggregate employment gap, the full GEGI is the weighted average of a “better employment gap” and “other employment gap.” The basic and full GEGIs are similar (correlation of 0.97), and both average 19 percent across countries. This means that GDP per capita in the long run would be almost 20 percent higher if female employment were exogenously increased to be the same as men’s (other things being equal). The paper also provides an application for the Pacific Islands, for which a simple measure like the GEGI is particularly important given the lack of alternative estimates.